Relação Pensamento-Linguagem e as Distorções Conceituais no Ensino de Biologia - Ceschim, Beatriz [UNESP]; Ganiko-dutra, Matheus [UNESP]; Caldeira, Ana Maria De Andrade [UNESP] (Programa de Pós-Graduação em Educação para a Ciência, Universidade Estadual Paulista (Unesp), Faculdade de Ciências, campus de Bauru., 2020)
The aim of this study was to investigate the misunderstandings produced by the relationship between thought and language in Biology Education, with the identification of variabilities that may interfere with didactic articulation. We have surveyed data from research both in progress and published over the last decade by the Epistemology of Biology Research Group of São Paulo State University (UNESP). This has allowed for the systematization of a set of identified variables, which can pose difficulty to the articulation of didactic, epistemological, cognitive and linguistic processes in the initial training/education of teachers of biological sciences and that may lead to the incomprehension of Biology as a science or its inter-relations. The results suggest that polysemy and figures of speech stimulate human thought to distort concepts that are contrary to Biological Epistemology.

O objetivo geral deste trabalho foi investigar as distorções conceituais decorrentes da relação pensamento-linguagem que ocorrem no Ensino de Biologia, identificando as variáveis que possam interferir na articulação didática. Realizou-se um levantamento, por meio de trabalhos, a partir das pesquisas em andamento e publicadas pelo Grupo de Pesquisa em Epistemologia da Biologia (GPEB), da Universidade Estadual Paulista Júlio de Mesquita Filho (UNESP) ao longo da última década, que permitiu sistematizar um conjunto de variáveis identificadas, dificultadoras da articulação didática, epistemológica, linguística e cognitiva na Formação Inicial de Professores em Ciências Biológicas e que resultam na não compreensão da Biologia como ciência e suas inter-relações. Os resultados sugeriram que a polissemia e as figuras de linguagem estimulam o pensamento humano a promover distorções conceituais que se opõem à Epistemologia da Biologia.
The Relation between Thought and Language, and Misunderstandings in the Teaching of Biology
Keywords: Biology teaching; Initial teacher training; Didactics; Epistemology; Cognitive processes; Ensino de Biologia; Formação inicial do professor; Didática; Epistemologia; Processo cognitivo